An Interpretative Phenomenological Analysis On The Narratives Of Best Performing Reading Teachers - Abasolo, Rafdi Saniel (Pascasarjana Universitas Negeri Makassar, 2025)
Aside from the hefty workload of teaching English on different grade levels and sections, Reading teachers are also weighed down by the additional load of teaching each pupil how to read, and honing students’ reading abilities, and assisting struggling readers. This study aimed to unearth the individual lived experiences of the best Reading teachers in the Division of Davao del Sur, Mindanao, Philippines. Specifically, the study aimed to identify their best practices in transforming non-readers into independent readers and to further interpret and make sense of the Reading teachers’ individual experiences through the perspective of the researcher. Seven participants took part in this study. Aside from the emerging personal experiential themes, results showed four super-ordinate themes: innovative use of learning domains, adherence to the CIP Principle, aspiring for self-fulfillment in developing an independent reader, and fostering family-school-community partnership.